Low Back Pain Exacerbated by Psychosocial Factors - Derebery, V. Jane (1986)
Patients with low back pain can pose a considerable challenge when there is evidence of a nonorganic or functional overlay. These patients can become frustrating examples of chronicity if proper guidelines in diagnosis and management are not followed. An exploration into the psychosocial factors affecting a patient is essential. Several simple questions and tests can facilitate this process. Significant organic lesions should be ruled out with a minimum of appropriate diagnostic procedures. A supportive and conservative treatment regimen with the goal of returning patients to full functioning as soon as possible is recommended. Patients should be encouraged to take an active role in their own treatment.